Electrically controlled cellular migration on a periodically micropatterned PEDOT:PSS conducting polymer platform. Issue 5 (27th August 2018) - ElMahmoudy, M.; Curto, V. F.; Ferro, M.; Hama, A.; Malliaras, G. G.; O'Connor, R. P.; Sanaur, S.
ABSTRACT: In the field of tissue engineering, the study of cellular adhesion and migration is of crucial interest. Conducting polymers such as poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) provide an outstanding interface with biology due to their soft nature, which is closer to the mechanical, chemical, and morphological properties of biological systems. In this work, periodically micropatterned PEDOT:PSS thin films are used as a platform to investigate cellular migration. Human cerebral microvascular endothelial cells (hCMEC) show alignment and linear motion along PEDOT:PSS microstripes of varying widths (10–30 μm). In addition, an electrochemical gradient is created on the PEDOT:PSS film along these microstripes to influence the cell behavior. hCMEC cells linearly change their velocities depending on the redox state of the conducting polymer film. This work demonstrates the potential of such conducting polymer platforms to combine, at the same time, several key physicochemical factors for controlling cellular migration. In the future, we envision that these conducting polymer platforms will deliver tools for tissue regeneration and lead to new opportunities in regenerative medicine. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47029. Abstract : Micropatterned PEDOT:PSS offers a promising platform for interfacing cells with electronics devices. In this study, we introduce the use of electrically driven PEDOT:PSS microstripes for controlling cell migration. First, our results show cells alignment on the PEDOT:PSS microstripes. Consequently, cells show a linear motion along the stripes, as well as a response to the electrochemical gradient created on the conducting film.